2011
DOI: 10.1002/jmv.22031
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and accurate detection system for infection by the 2009 pandemic influenza A (H1N1) virus with a pocket-warmer reverse-transcriptase loop-mediated isothermal amplification

Abstract: The 2009 pandemic H1N1 influenza A virus spread quickly worldwide in 2009. Since most of the fatal cases were reported in developing countries, rapid and accurate diagnosis methods that are usable in poorly equipped laboratories are necessary. In this study, a mobile detection system for the 2009 H1N1 influenza A virus was developed using a reverse-transcriptase loop-mediated isothermal amplification (RT-LAMP) kit with a disposable pocket-warmer as a heating device (designated as pwRT-LAMP). The pwRT-LAMP can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…In a similar approach, an electricity-free cartridge was integrated with LFT for HIV detection with a sensitivity of 6 copies/ μ L. 94 It was also shown that even a pocket hand warmer could be used for LAMP amplification. 95 Zhang et al 96 used a pocket warmer and capillary glass for LAMP-based multiplexing target NAs. Various target DNAs and negative controls were injected at different positions of the channel, and the two sides of the channel were sealed with epoxy glue.…”
Section: Design Criteriamentioning
confidence: 99%
“…In a similar approach, an electricity-free cartridge was integrated with LFT for HIV detection with a sensitivity of 6 copies/ μ L. 94 It was also shown that even a pocket hand warmer could be used for LAMP amplification. 95 Zhang et al 96 used a pocket warmer and capillary glass for LAMP-based multiplexing target NAs. Various target DNAs and negative controls were injected at different positions of the channel, and the two sides of the channel were sealed with epoxy glue.…”
Section: Design Criteriamentioning
confidence: 99%
“…The most useful laboratory test for the clinical management of A/2009/H1N1 influenza is nucleic acid amplification after reverse transcription (Table 11). In 10 studies, the overall reported sensitivity of real-time RT-PCR ranged from 90.5% to 97.6% (60,202,240,286,321,336,404,422,432,559). The majority of the studies reported a specificity of 100%, with four exceptions (60,404,432,559).…”
Section: Nucleic Acid Amplificationmentioning
confidence: 99%
“…As a result, this technology has been used widely for molecular detection of several microorganisms, including clinical and plant-associated bacterial [32,[61][62][63][64][65][66][67][68][69][70][71][72][73], fungal [74][75][76], viral [47,[77][78][79][80][81][82][83][84], and parasitic [57,59,[85][86][87][88] pathogens, and is therefore suitable as a rapid field test.…”
Section: Discussionmentioning
confidence: 99%